Comparison of Pain Tolerance between Opioid Dependent Patients on Methadone Maintenance Therapy (MMT) and Opioid Naive Individuals - Zalina Zahari; Chee Siong Lee; Muslih Abdulkarim Ibrahim; Nurfadhlina Musa; Mohd Azhar Mohd Yasin; Yeong Yeh Lee; Soo Choon Tan; Nasir Mohamad; Rusli Ismail (Frontiers Media S.A., 2016)
Purpose: This study compared pain sensitivity among opioid dependent patients on methadone maintenance therapy (MMT) and opioid naive subjects. Methods: The three hundred participants comprised 152 opioid naive subjects and 148 opioid dependent patients. Opioid naive subjects had not taken any opioids including morphine and methadone to their best knowledge and were presumed so after two consecutive negative urine screenings for drugs. All opioid dependent patients were stabilized in treatment, defined as having been enrolled in the program for more than one month with no change of methadone dosage over the past one month. Excluded from the study were individuals with chronic or ongoing acute pain and individuals with a history of analgesics ingestion within 3 d before the cold pressor test (CPT). Pain tolerance to CPT was evaluated at 0 h, and at 2, 4, 8, 12, and 24 h post-methadone dose. Results: Patients exhibited a significantly shorter mean pain tolerance time of 34.17 s (95% CI 24.86, 43.49) versus 61.36 (52.23, 70.48) [p < 0.001] compared with opioid naive subjects. Time-dependent mean pain tolerance was also significantly different when naive subjects were compared to patients (p = 0.016). Conclusions: This study revealed hyperalgesia amongst patients on MMT, as manifested by their quicker hand withdrawal. The complaints of pain in this population should not be underestimated and the pain should be evaluated seriously and managed aggressively.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.